Life under pressure: the social roots of youth suicide and what to do about them - Mueller, Anna S. (Oxford University Press, 2024)
"During her junior year at Poplar Grove High School, Aria found herself sliding into a worsening depression. She had what she described as the perfect life, including fabulous vacations, her dream car, and more importantly, a big loving family, close friends, and a boyfriend she adored, but daily life had become unbearable. Though she knew how badly her suicide would hurt everyone around her, her psychological pain ultimately overwhelmed her. Aria ended her life twelve days after she started her journal, excerpted with her parents' permission, above"--